Inventarisasi dan Pengembangan Potensi Cagar Budaya Kota Baubau - Dinna Dayana La Ode Malim; Iwan Sumantri; Supriadi; Tasrifin Tahara (Balitbangda Kota Baubau, 2019)
This article aims to inventory the potential of cultural heritage, as well as document and classify data on the potential of the city's cultural heritage. The implementation of this activity is carried out through procedural steps in conducting studies in the preparation of plans which include field surveys, data processing, and analysis. This study also begins with an overview of the City of Baubau from various aspects, especially regional economics, society, (human resources and population), and aspects related to the cultural heritage of the City of Baubau then carries out an analysis related to the development policy of Baubau City. In terms of inventorying potential cultural heritage based on the development phase of the City of Baubau since the Kingdom/Buton Sultanate. Furthermore, the existing conditions related to cultural preservation included basic information, cultural heritage potential, documentation, and classification of cultural heritage spaces for cultural development in the City of Baubau.